2017
DOI: 10.24200/sci.2017.4484
|View full text |Cite
|
Sign up to set email alerts
|

A simple solution procedure to solve the multi-delivery policy into economic production lot size problem with partial rework

Abstract: Abstract. Recently, an alternative multi-delivery policy into imperfect EconomicProduction Quantity (EPQ) inventory model with partial rework has been proposed, which considers the number of shipments as a xed and given value. This paper, treating the longrun average costs per unit time as a function of replenishment lot size Q and the number of shipments n, adopts the di erential calculus approach to get the optimal solution of Q and n jointly. In numerical examples, it is illustrated that the solution proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…[46] studied replenishment and pricing strategies for a defective process with paramount rework and various deliveries. [47] solved the multi-delivery lot-sizing dilemma with a partial rework. [6] proposed a lot-sizing model for a production system with back-ordering and outsourcing rework.…”
Section: Reworkmentioning
confidence: 99%
“…[46] studied replenishment and pricing strategies for a defective process with paramount rework and various deliveries. [47] solved the multi-delivery lot-sizing dilemma with a partial rework. [6] proposed a lot-sizing model for a production system with back-ordering and outsourcing rework.…”
Section: Reworkmentioning
confidence: 99%
“…Wang et al [41] also proposed an optimal order quantity model, taking into account the screening constraints. Jaggi et al [42], Moussawi-Haidar et al [43], Liao [44], Pal et al [45], Shah et al [46], Sekar and Uthayakumar [47], Benkherouf et al [48], Chen [49], Sha ee-Gol et al [50], Jawla and Singh [51], C ardenas-Barr on et al [52], Nobil et al [53], Chung et al [54], and Nobil et al [55] have recently explored the area of inventory management by employing various rework scenarios.…”
Section: Motivationmentioning
confidence: 99%
“…A multi objective close loop sustainable SC network model based on logistic discount supposition was formulated by Fathollahi-Fard and Hajiaghaei-Keshteli [7]. Since 1990s, researchers have shown that discount available due to fleet selection will decrease the price of perishable product at the hand of end customer, by decreasing the logistic cost of manufacturers [51][52].…”
Section: Fleet Selectionmentioning
confidence: 99%